Analisis Pengaruh Sektor Pariwisata Dalam Pembangunan di Kabupaten Nagekeo - Lende, Wilhelmina Y A; Penu, Yustina; Djata, Baltasar (Program Studi Ekonomi Pembangunan Universitas Flores, 2021)
This study aims to determine the influence of the tourism sector on development in Nagekeo Regency through data sourced from the Nagekeo Regency Tourism Office with calculations using the SPSS 23 Program. The analysis technique used is multiple linear regression. To calculate the multiple linear regression equation, the data must meet the basic assumption test, namely through the classical assumption test and hypothesis testing. The results of this study indicate that: the first variable of the hotel and restaurant tourism sector tax has a positive effect on the development variable. This is evidenced by the results of the individual parametric significance test (t test). The value of tcount ttable (5.636 2.015). The two variables of employment have a positive effect on the development variable with a value of tcount ttable (3.215 2.015). Then for the F test, the value of Fcount Ftable (9.529 5.79). This means that the tourism sector tax and employment together have a significant effect on development. The development of the tourism sector is directed at the development of the hotel or lodging and restaurant sectors around community-based tourist destinations.